Fluorescent Nanozeolite Receptors for the Highly Selective and Sensitive Detection of Neurotransmitters in Water and Biofluids (Adv. Mater. 49/2021). Issue 49 (7th December 2021) - Grimm, Laura M.; Sinn, Stephan; Krstić, Marjan; D'Este, Elisa; Sonntag, Ivo; Prasetyanto, Eko Adi; Kuner, Thomas; Wenzel, Wolfgang; De Cola, Luisa; Biedermann, Frank
Abstract : Detection of Neurotransmitters So far, only modestly performing synthetic binders have been accessible for small bioactive molecules such as serotonin and dopamine. In article number 2104614, Luisa De Cola, Frank Biedermann, and co‐workers introduce zeolite‐based artificial receptors (ZARs), which are microporous inorganic–organic hybrid materials applicable for the optical‐based detection of serotonin and dopamine in urine at physiological relevant concentrations. These ZARs outperform protein receptors with respect to response times, robustness and scalability.